2022
DOI: 10.3390/ijms23126561
|View full text |Cite
|
Sign up to set email alerts
|

Novel Insight into the Potential Role of Acylglycerophosphate Acyltransferases Family Members on Triacylglycerols Synthesis in Buffalo

Abstract: Acylglycerophosphate acyltransferases (AGPATs) are the rate-limiting enzymes for the de novo pathway of triacylglycerols (TAG) synthesis. Although AGPATs have been extensively explored by evolution, expression and functional studies, little is known on functional characterization of how many members of the AGPAT family are involved in TAG synthesis and their impact on the cell proliferation and apoptosis. Here, 13 AGPAT genes in buffalo were identified, of which 12 AGPAT gene pairs were orthologous between buf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 47 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…Among them, the expressions of AGPAT2 and AGPAT5 are too low for further functional analysis. The functions of AGPAT1 and AGPAT6 in BMECs have been studied in a previous report [9,33]. We selected AGPAT1 to compare this study with the previous report.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among them, the expressions of AGPAT2 and AGPAT5 are too low for further functional analysis. The functions of AGPAT1 and AGPAT6 in BMECs have been studied in a previous report [9,33]. We selected AGPAT1 to compare this study with the previous report.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, current studies have mainly focused on the role of the AGPAT gene family in regulating milk fat content, with few investigating its role in regulating fat composition. In a previous study, the authors identified 32 and 14 AGPAT isoform protein sequences encoded by 13 AGPAT genes predicted from the river and swamp buffalo genomes, respectively [9]. However, most of the identified AGPAT genes are only predicted by sequence analysis, and cannot be amplified from the mRNA of MFG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Identification of functional markers for milk production traits has drawn significant attention from the scientific community and breeders. ,, Previous studies have demonstrated that ACAA1 polymorphism was associated with breast cancer risk and loin-eye area in beef. , However, the association between ACAA1 polymorphism and milk production remains unclear. In this study, we identified five SNPs in the buffalo ACAA1 gene, of which three SNPs were associated with milk production traits.…”
Section: Discussionmentioning
confidence: 99%
“…Identification of functional markers for milk production traits has drawn significant attention from the scientific community and breeders. 49,50,53 Previous studies have demonstrated that ACAA1 polymorphism was associated with breast cancer risk and loin-eye area in beef. 50,51 However, the association between ACAA1 polymorphism and milk production remains unclear.…”
Section: ■ Discussionmentioning
confidence: 99%